الحداثة السياسية: من التأسيس للعنف إلى تفكيك مفارقاته - محمد الصادق بلام (مجلة الآداب و العلوم الإجتماعية, 2016)
This paper aims to address one of the current problems concerning the issue of violence inhuman phenomenon rooted in human history and endemic in reality of life as a political and social behavior.